Use and exchange of aquatic resources relevant for food and aquaculture: common carp ( Cyprinus carpio L.) - Zsigmond Jeney; Zhu Jian (Reviews in Aquaculture, 2009)
This review describes the genetic resources of common carp relevant for food through fisheries and aquaculture. Common carp is naturally distributed in a large part of Asia and Europe and has been introduced worldwide and is reputed to have been cultured for centuries. Its status in Asia and Europe is discussed in detail. The rich diversity of carp in Asian aquaculture is described, with an emphasis on China, the largest producer in the world. In Central and Eastern Europe common carp is the most important ‘freshwater species’, and 60 ‘national’ and 25 ‘foreign’ strains are described in the most recent Catalogue of Carp Breeds ( Bogeruk 2008 ). There are different systems for the management and conservation of carp genetic diversity depending on the level of state involvement, and these systems are described for selected countries/regions, such as China and central and eastern European countries. The latter countries are in a current ‘transition period’ and a tendency of ‘state‐withdrawal’ is evident. However, it is not yet clear whether the market alone is able/ready to take over the responsibility and cost of the management and conservation of carp genetic diversity.